Systemic Lupus Erythematosus Presenting with Alveolar Hemorrhage - Omar Tolaymat; Florentina Berianu (Case Reports in Rheumatology)
Introduction. Diffuse alveolar hemorrhage is a rare presentation of systemic lupus erythematosus. Early diagnosis and appropriate treatment can improve outcome. Case Report. An 18-year-old male presented with hemoptysis and respiratory distress requiring orotracheal intubation. Laboratory tests showed positive anti-nuclear antibody and anti-dsDNA and low C3 and C4. Bronchoalveolar lavage became progressively hemorrhagic after each aliquot. He was treated with pulse methylprednisolone, cyclophosphamide, and plasma exchanges. Discussion. Alveolar hemorrhage is a rare initial presentation of lupus, with mortality rates reported at about 50%. Lupus should be considered in those presenting with alveolar hemorrhage since delay in therapy may cause a rapid deterioration of the patient. The diagnosis of SLE is illusive when DAH is the presenting symptom. Since early diagnosis and appropriate institution of treatment improve outcome, it is important to keep lupus in mind as an etiology of alveolar hemorrhage. Pulse methylprednisolone, cyclophosphamide, and plasmapheresis therapy resulted in rapid improvement of respiratory function in our patient.